ASSESSMENT OF THE REACTIVE HYPERAEMIA THROUGH QUANTIFICATION OF COLOUR CHANGES USING PIXEL ANALYSIS SOFTWARE - T. Tanwi; S. Manjunatha; B. Priya (European Scientific Journal, ESJ, 2013)
A sound cardiovascular system is essential for human health. There are many effective tests to measure cardiac performance, but no matching test exists to detect vascular reactivity. Hence the acute need for a sensitive, non-invasive, cost-effective screening test. The present study purports such a method of assessing variation in blood flow by quantifying colour changes visible in palm secondary to reactive hyperaemia for detection of presence of vascular lesions. Colour changes in palms of test and control hands were recorded in healthy young volunteers (5 males, 5 females) by taking a series of photographs at 5 seconds interval in pre, during and post occlusion periods. Sphygmomanometer was used to produce arterial occlusion in test hand. The colour changes were analysed for red pixels by indigenously developed colour analysis software “Chitradeepam”. Mean of values for each hand in above-mentioned periods were calculated for all subjects and corresponding values of test and control hands were compared using student’s t test. No difference was observed in baseline values of both hands. During occlusion, there was significant decrease in test hand colour in females compared to their control hand but not in males. Post occlusion, significant colour increase was observed in test hands of males compared to control. A similar trend, though statistically not significant was seen in females. This technique can be useful in determining normal vascular response in healthy individuals through quantification of reactive hyperaemia which in turn can be a parameter to assess the decreased vascular response in Peripheral Vascular Disease.